Combining spatial planning and ecosystem services value to assist ecological compensation decision-making—A case study of Yangtze River Delta ecological barrier, China - Wang, Ziyi; Wang, Yu; Zhou, Zihang; Yu, Fan; Ma, Debin; Li, Jiaming (Frontiers in Environmental Science, 2022)
China's ecological compensation (EC) is based on the property rights structure of public ownership of natural resources, which is used not only as a logical starting point of spatial planning, but also as an important tool to clarify property rights management boundaries and allocate development rights by local governments. This study combined spatial planning and ecosystem service value accounting to design a decision-making framework for EC. We selected 32 counties (districts) in the Yangtze River Delta region as the research object with the consideration of spatial planning and expert advice, and found that the implementation of EC slowed down the urbanization process and promoted the increase of ecological space. We calculated and prioritized the spatio-temporal changes of ecosystem service value in the region from 2000 to 2019. The results show that the total amount of EC research area in 2019 is 38.098 billion CNY, accounting for 9% of the region's GDP. Among the 32 compensated areas, Shitai County, China, has the highest priority. We believe that this decision-making framework has the potential to be applied to the implementation of EC in other regions of China. At the same time, it can also be used to enrich the international views on EC research.